Larvicidal efficacy and biological stability of a botanical natural product, zedoary oil-impregnated sand granules, against Aedes aegypti (Diptera, Culicidae) - Daruna Champakaew (2018)
Chemical analysis on Curcuma zedoaria rhizome volatile oil, using gas chromatography-mass spectrometer techniques, demonstrated the presence of β-tumerone (19.88%), 1,8-cineole (8.93%), and 7-zingiberene (7.84%) as major constituents. Larvicidal efficacy against Aedes aegypti mosquitoes of zedoary oil and its formulated preparation, zedoary oil-impregnated sand granules, were investigated and compared with that of Abate®sand (temephos). Zedoary oil exhibited pronounced potential against the fourth instar larvae of A. aegypti with an LC50and LC99of 33.45 and 83.39 ppm, respectively. Application of zedoary oil at a dosage yielding ten times that of LC99offered complete larval mortality (100% mortality) for a period of 3 days, and the larval mortality subsequently decreased to lower than 50% after application for more than 5 days. Zedoary oil-impregnated sand granules provided remarkably longer activity, with a larval mortality of 100% for a period of 9 days; and mortality below 50% was obtained in week 3 of application. The complete larval mortality that resulted from applying temephos at dosages of 0.1 and 1 ppm persisted for a period of 6 days and 4 weeks, respectively, and the larval mortality below 50% was reported on day 18 and week 11, respectively. Testing A. aegypti species against stored samples of zedoary oil-impregnated sand granules demonstrated that the product stored at 4°C showed the longest larvicidal activity, followed by those kept at ambient temperature and 45°C, yielding a complete larval mortality for 9, 8, and 6 days, respectively. Most samples of zedoary oil-impregnated sand granules stored at each temperature for 1 month showed slightly higher efficacy than those kept for 2 months. The larvicidal efficacy of samples stored at 4°C seemed to be comparable to that of the fresh sample. The efficacy in killing A. aegypti larvae and good biological stability of zedoary oil-impregnated sand granules make this product promising as an alternative to essential oil in the development of new botanical natural larvicide for use in mosquito control programs. © 2006 Springer-Verlag.